Cyanobacteria and Cyanotoxin in the Billings Reservoir (São Paulo, SP, Brazil) - Moschini-Carlos, Viviane [UNESP] (2009)
The Billings Complex and the Guarapiranga System are important strategic reservoirs for the city of São Paulo and surrounding areas because the water is used among other things, for the public water supply. They produce 19,000 liters of water per second and Supply water to 5.4 million people. Crude water is transferred from the Taquacetuba branch of the Billings Complex to the Guarapiranga Reservoir to regulate the water level of the reservoir. The objective of this study was to evaluate the water quality in the Taquacetuba branch, focusing on cyanobacteria and cyanotoxins. Surface water samples were collected in February (summer) and July (winter) of 2007. Analyses were conducted of physical, chemical, and biological variables of he water, cyanobacteria richness and density, and the presence of cyanotoxins. The water was classified as eutrophic-hypereutrophic. Cyanobacteria blooms were observed in both collection periods. The cyanobacteria bloom was most significant in July, reflecting lower water transparency and higher levels of total solids, suspended organic matter, chlorophyll-a, and cyanobacteria density in the surface water. Low richness and elevated dominance of the cyanobacteria were found in both periods. Cylindrospermopsis raciborskii was dominant in February, with 352 661.0 cel mL(-1), and Microcystis panniformis was dominant in July, with 1 866 725.0 cel mL(-1). Three variants of microcystin were found in February (MC-RR, MC-LR, MC-YR), as well as saxitoxin. The same variants of microcystin were found in July, but no saxitoxin was detected. Anatoxin-a and cylindropermopsin were not detected in either period. These findings are of great concern because the water in the Taquacetuba branch, which is transferred into the Guarapiranga Reservoir, is not treated nor managed. It is recommended that monitoring be intensified and more effective measures be taken by the responsible agencies to prevent the process of eutrophication and the consequent development of the cyanobacteria and their toxins.